12 Assessment of individual responses to P2Y12 inhibitors: validation of a new point of care test & a novel rapid analysis. (25th January 2018) - Olechowski, Bartosz; Dalton, Richard T; Khanna, Vikram; Vavyla, Maria; Ashby, Alexander; Mariathas, Mark; Harris, Scott; Nicholas, Zoe; Mahmoudi, Michael; Curzen, Nick
Abstract : Introduction: There is potential value in testing individual response to P2Y12 inhibitors in order to predict ischaemic and bleeding risk in PCI patients. We aimed to: a) validate the ability of a novel point of care (POC) assay using thrombelastography, TEG6s, to detect changes in ADP-induced whole blood clotting and b) compare a novel, rapid test parameter, area under the curve at 15 min (AUC15), with the traditional maximum clot amplitude (MA). Methods: 25 participants were included in whom ADP-induced clotting was measured at 4 time points: a) 12 healthy volunteers given 600 mg of clopidogrel; b) 12 patients with ACS given 600 mg of clopidogrel; c) 1 healthy volunteer given 600 mg of clopidogrel on 5 separate occasions. All samples were tested using traditional TEG5000 and the new point of care TEG6S. Results: TEG 5000 and TEG 6 s detected changes in ADP–induced clotting. Bland Altman analysis demonstrated a good level of agreement between them [figure 1a]. For TEG6S, correlation between MA & our novel AUC15 was strong for both thrombin and ADP channels [figure 1b] (R=0.867, R=0.936, p<0.001), & the AUC15 result was available on average 13.3 mins earlier. Conclusions: TEG6s is a rapid, easy to use and accurate test of ADP-induced clotting using TEG5000 as a reference. A novel parameter, AUC15, is a viable and time saving option for this POC test.